2014
DOI: 10.1056/nejmoa1404731
|View full text |Cite
|
Sign up to set email alerts
|

Atenolol versus Losartan in Children and Young Adults with Marfan's Syndrome

Abstract: BACKGROUND Aortic-root dissection is the leading cause of death in Marfan's syndrome. Studies suggest that with regard to slowing aortic-root enlargement, losartan may be more effective than beta-blockers, the current standard therapy in most centers. METHODS We conducted a randomized trial comparing losartan with atenolol in children and young adults with Marfan's syndrome. The primary outcome was the rate of aortic-root enlargement, expressed as the change in the maximum aortic-root-diameter z score indexe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
212
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 455 publications
(221 citation statements)
references
References 29 publications
6
212
0
3
Order By: Relevance
“…The prominent role of AngII in cardiovascular remodeling has positioned renin angiotensin aldosterone system antagonists as front‐line therapy for ATAA, LVH, and advanced AVS52, 53, 54; however, systemic therapy with AngII receptor blockers or angiotensin‐converting enzyme inhibitors have achieved limited success, especially in attenuating ATAA expansion and AVS progression. In contrast, we have witnessed promising results in AngII‐infused mice receiving LepA at the ascending aorta.…”
Section: Discussionmentioning
confidence: 99%
“…The prominent role of AngII in cardiovascular remodeling has positioned renin angiotensin aldosterone system antagonists as front‐line therapy for ATAA, LVH, and advanced AVS52, 53, 54; however, systemic therapy with AngII receptor blockers or angiotensin‐converting enzyme inhibitors have achieved limited success, especially in attenuating ATAA expansion and AVS progression. In contrast, we have witnessed promising results in AngII‐infused mice receiving LepA at the ascending aorta.…”
Section: Discussionmentioning
confidence: 99%
“…75,103,104 Targeted questions in cardiac surgical practice and pharmacological treatment of CHD, Kawasaki disease, and Marfan syndrome have been addressed using high-quality randomized clinical trials under the auspices of the PHN. 12,13,[105][106][107] New approaches to investigation of clinical practice are likely to increasingly use models of collaborative, structured learning in the field, such as Standardized Clinical Assessment and Management Plans, which have proved valuable in collecting and analyzing data on common conditions in which there is significant variation of clinical practice. [109][110][111] In addition, registries (see below) will continue to enable research on conditions that are not well suited to randomized, controlled trials.…”
Section: Evidence-based Practice and Outcomes Researchmentioning
confidence: 99%
“…These promising findings have fuelled the development of several randomised trials to evaluate the effect of losartan upon aortic morbidity and mortality in patients with Marfan syndrome 88. However, a randomised study has recently shown in 608 patients (children and young adults) with Marfan syndrome that losartan did not alter the rate of aortic root dilatation 89. Whether angiotensin II type 1 receptors play a significant role in BAV‐associated aortopathy remains to be investigated.…”
Section: Pathobiologymentioning
confidence: 99%